2010
DOI: 10.2111/rem-d-09-00087.1
|View full text |Cite
|
Sign up to set email alerts
|

Supplements Containing Escape Protein Improve Redberry Juniper Intake by Goats

Abstract: Redberry juniper (Juniperus pinchotii Sudw.) is a common invasive plant species in west-central Texas. Goats will consume redberry juniper, but intake is limited by monoterpenoids found in the plant. Previous research has shown that goats will increase juniper intake through 1) conditioning and 2) protein supplementation. This study compared intake of juniper when goats received different protein supplements either with or without protein sources that are high in amino acids that escape digestion in the rumen.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
(39 reference statements)
0
6
1
Order By: Relevance
“…Protein supplementation did not improve juniper consumption by lambs in the second trial. It is unclear why protein supplementation apparently increased intake of juniper by goats as reported by George et al (2010) but did not increase juniper by lambs in the current study.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Protein supplementation did not improve juniper consumption by lambs in the second trial. It is unclear why protein supplementation apparently increased intake of juniper by goats as reported by George et al (2010) but did not increase juniper by lambs in the current study.…”
Section: Discussioncontrasting
confidence: 54%
“…Future research should determine if sheep will continue to consume juniper when released into the pasture after weaning. In addition, recent research with goats has suggested that supplements formulated with protein sources that partially escape digestion in the rumen might further improve juniper consumption (George et al 2010). Protein supplementation did not improve juniper consumption by lambs in the second trial.…”
Section: Discussionmentioning
confidence: 79%
“…To increase redberry juniper (Juniperus pinchotii) intake, protein supplementation is often suggested (Illius and Jessop 1995; Pritz et al 1997; Estell et al 2018). However, the literature is inconsistent on whether rumen degradable protein (RDP) or rumen undegradable protein (RUP) is more important for goats consuming one-seed (Juniperus monosperma) and redberry juniper (Campbell et al 2007; Utsumi et al 2009; George et al 2010; Miller and Scott 2021). While RDP would be available to rumen microbes, RUP that bypasses the rumen may increase amino acids available to the hindgut and liver for PSM detoxification (Foley et al 1995; George et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, the literature is inconsistent on whether rumen degradable protein (RDP) or rumen undegradable protein (RUP) is more important for goats consuming one-seed (Juniperus monosperma) and redberry juniper (Campbell et al 2007; Utsumi et al 2009; George et al 2010; Miller and Scott 2021). While RDP would be available to rumen microbes, RUP that bypasses the rumen may increase amino acids available to the hindgut and liver for PSM detoxification (Foley et al 1995; George et al 2010). Dried distiller's grain (DDG) is a common high RUP protein source in the midwestern United States (National Research Council 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It appears that most of the toxins in juniper are partially oxidized in the liver and conjugated with gluconurides in the liver and excreted (Foley et al 1995;Dunson et al 2007;George et al 2010). However, redberry juniper contains 16 identified monterpenoids, and ashe juniper contains 17 identified monoterpenoids (Owens et al 1998;Dietz et al 2010).…”
Section: Introductionmentioning
confidence: 99%